2001
DOI: 10.1111/j.1745-459x.2001.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Chinese‐origin and European‐origin Australian Consumers’ Texture Preferences Using a Novel Extruded Product

Abstract: Diverse food choices and preferences are commonly observed between consumers cross-culturally, however, many aspects of these behavioral differences are not yet fully understood. In order to investigate cross-cultural texture preferences, six extruded snack samples, manufactured under different processing conditions to represent a range of textural characteristics were characterized by a trained panel using descriptive sensory analysis. In parallel, thirty-eight naive European-Origin and thirty-seven naive Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Scales to assess their preferences were not used because people, particularly from different cultures, may use them differently. For example, it has been shown that Asians are more likely to avoid the extremes of hedonic scales when compared to other ethnic groups (Yeh et al, 1998) and a cultural bias was observed between Chinese-origin and European-origin Australian consumers in the use of line scales (Murray, Easton, & Best, 2001). A measure of importance was made by having Ôhidden replicationÕ of appearance characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Scales to assess their preferences were not used because people, particularly from different cultures, may use them differently. For example, it has been shown that Asians are more likely to avoid the extremes of hedonic scales when compared to other ethnic groups (Yeh et al, 1998) and a cultural bias was observed between Chinese-origin and European-origin Australian consumers in the use of line scales (Murray, Easton, & Best, 2001). A measure of importance was made by having Ôhidden replicationÕ of appearance characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…There were also reports on textural preference between cultures, e.g., Jaeger et al. (1998) on preference patterns for mealiness among British and Danish consumers, and Murray et al. (2000) on the textural preferences of European and Chinese consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of these differences has been provided by investigations of cross-cultural differences in food preferences among consumers in different countries, including the study of British and Danish consumer preferences for different levels of apple mealiness (Jaeger, Andani, Wakeling, & MacFie, 1998), preferences for plain chocolate amongst Polish and Belgian consumers (Januszewska & Viaene, 2001) and American and Spanish consumer preferences for sweets and beverages (Zellner, Garriga-Trillo, Rohm, Centeno, & Parker, 1999). Cultural differences within a country have also been reported, such as snack texture preferences amongst Australian consumers of Chinese-and European-origin (Murray, Easton, & Best, 2001) or apple labelling preferences of New Zealand and Samoan consumers resident in New Zealand (Jaeger, 2000).…”
Section: Introductionmentioning
confidence: 96%